Living downwind from corporate social responsibility: a community perspective on corporate practice - Brueckner, Martin; Mamun, M. (Blackwell Publishing Ltd, 2010)
This paper critiques dominant corporate social responsibility (CSR) theory, which claims that commercial and social goals overlap and coincide. It is suggested that this uncritical portrayal and treatment of complex industry–community relations risks neglecting the potential tensions that may arise should these goals diverge or be in conflict. In this context, the experiences of residents in a small Western Australian town are presented to describe a long-running conflict between community members and their corporate neighbour. The data point to a range of community impacts as a result of corporate activities and unearth strong differences between ‘local’ and ‘corporate’ understandings of CSR. Based on the perceived shortcomings of an economically underpinned CSR approach, we question the possibility of meeting local needs by means of economic efficiency. Calls are made for critical reflection on the key assumptions underlying dominant CSR theory and consideration is given to questions of guidance for CSR practitioners.